The implementation of the environmental impact assessment in Fukushima contaminated water discharge: an analysis of the international legal framework - Chen, Xidi; Xu, Qi (Frontiers in Marine Science, 2024)
Japan is discharging nuclear contaminated water from the 2011 Fukushima incident into the sea after treatment with the Advanced Liquid Processing System (ALPS). This process is expected to continue for decades, as planned by the Japanese government. This decision sparks opposition from many countries and international organizations, as well as constant protests from people in Japan and neighboring countries. Although there are no international documents specifically addressing the discharge of contaminants from a nuclear accident, it is found that the LOS Convention, treaties on nuclear safety, and international environmental laws provide the basis and legal framework for requiring Japan to implement environmental impact assessments throughout the entire process of Fukushima contaminated water discharge. First, this paper evaluates the consistency between the measures taken before Japan’s decision to discharge contaminated water into the sea and the requirements under international laws. Second, this paper further examines the substantive and procedural requirements under international law for the entire process of Fukushima contaminated water discharge. It identifies substantive criteria to be applied in assessing the environmental impact of Fukushima contaminated water discharge based on international documents and explores the procedural requirements to assure transparency, prudence, and accountability of the assessment. Finally, given the potential transboundary damage caused by the discharge of nuclear-contaminated water into the sea, this paper proposes that a new multi-stakeholder cooperative mechanism is necessary to achieve effective and credible monitoring and respond to the claims of potentially affected parties. In addition to providing a legal framework for the environmental impact assessment in the Fukushima case, this paper may also contribute to the proper disposal of nuclear contaminants in future nuclear accidents.